Winterhouse - Guterson, Ben (Guterson, Ben. Winterhouse trilogy, 2018)
Orphan Elizabeth Somers's malevolent aunt Purdy and uncle Burlap ship her off to the ominous Winterhouse hotel, owned by the peculiar Norbridge Falls. Upon arrival, Elizabeth quickly discovers that Winterhouse has many charms - most notably its massive library. It's not long before she locates a magical book of puzzles that will unlock a mystery involving Norbridge and his sinister family. But as she uncovers the hotel's secrets, Elizabeth starts to realize that she is somehow connected to Winterhouse, for better or for worse. Mystery, adventure, and beautiful writing combine in this exciting debut set within a hotel full of secrets.